Peran Efikasi Diri Dan Harga Diri Terhadap Kesejahteraan Psikologis Siswa Kelas XII Di SMA Negeri 1 Tabanan - Prastita, Putu Tasya Pradnya Adi; Susilawati, Luh Kadek Pande Ary (Jurnal Ilmiah Wahana Pendidikan, 2024)
One of the developmental tasks for XII-grade students is determining their career after graduating from high school. The reality shows that many high school students still cannot determine their future career after graduating high school, which can be seen from the difficulty of students deciding between continuing their studies to university or going to work. This is caused by a lack of education regarding career planning held by each school. The inability of XII-grade high school students to determine career planning will impact the students' low psychological well-being. Two factors that influence students' psychological well-being are self-efficacy and self-esteem. This research examines the role of self-efficacy and self-esteem on the psychological well-being of XII-grade teenagers at SMA Negeri 1 Tabanan. This research involved 132 XII-grade students at SMA Negeri 1 Tabanan. This research used non-probability sampling techniques of incidental sampling. The Psychological Well-Being Scale has an Alpha coefficient of 0,946, the Self-Efficacy Scale has an Alpha coefficient of 0,876, and the Self-Esteem Scale has an Alpha coefficient of 0,649. The results of this study state that self-efficacy and self-esteem together play a significant role in psychological well-being. Apart from that, self-efficacy plays a significant positive role in improving psychological well-being and self-esteem does not play a significant role in improving psychological well-being.